(untitled) (International Current Pharmaceutical Journal, 2012)
Cancer chemotherapy engenders a gamut of unpredictable and perilous toxicities, which can cause substantialmortality, morbidity, and results in escalated healthcare costs due to increased requirement for ameliorative treat-ments and toxicity-related hospitalization. The main objective of this article is to report a range of adverse effects ofCHOP regimen in patients with intermediate grade Non-Hodgkins Lymphoma (NHL). This randomized prospective study was conducted on de novo intermediate grade NHL patients, aged >20?60 years, receiving CHOP chemotherapyregimen. Out of 30 patients who satisfied the inclusion criteria, only 25 patients completed 6 cycles of chemotherapy and were evaluated for various toxicities. Evaluation of all the 25 subjects showed that, in comparison with the baseline, most patients exhibited toxic damages. The hepatopancreatic, dermatological, vascular and nephrologicaldamages, eventually resulted in weight loss, hepatomegaly, alopecia, hypotension, as well as abnormal levels of serum liver markers, serum creatinine and blood glucose. But, the necessity to interrupt the CHOP treatment did not arise in any of the patients. Thus, in this study combination chemotherapy with CHOP protocol was well tolerated by majority of the subjects. DOI: http://dx.doi.org/10.3329/icpj.v1i10.11850 International Current Pharmaceutical Journal 2012, 1(10): 322-327